THE RELATIONSHIP BETWEEN LEARNING DELIVERY STRATEGY TOWARDS LEARNING ACHIEVEMENT OF CULTURAL ARTS AND CRAFTS OF CLASS IV STUDENTS OF SDN PETIR 4 TANGERANG CITY - Maya Agustina; Eka Yulyawan Kurniawan; Sunaryo . (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This study aims to determine whether there is a relationship between learning delivery strategies on learning achievement in arts and crafts. This type of research uses a quantitative approach to the survey method. The population is fourth grade students at SDN Petir 4, Tangerang City, with a total of 80 students. The sample used was 40 students. The data collection technique consisted of even semester grade IV students at SDN Petir 4 and 30 items of learning delivery strategy statements using a Likert scale with 4 scales. To test the hypothesis, the correlation coefficient test was used to obtain a t_(table) value of 2.024. That the results of the t test for the learning delivery strategy obtained t_(count) = 2.200 > 2.024 with a significance of 0.00 <0.05. So it can be concluded that there is a relationship between learning delivery strategies on student achievement and the contribution of student learning delivery strategies of 11.2%. Thus a significant positive relationship between high learning delivery strategies means that student achievement will also be higher.